Credit card fraud detection using machine learning techniques - Kabir, Tasmia; Nishat, Tahnin; Tory, Saria Bulbul (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2021.